A Spaceborne Wide-Area Surveillance Mode and Its Application in Maritime Monitoring - Shi-Chao Zheng; Hong-Jun Song; Robert Wang; Yun-Hua Luo; Kun Wu (International Journal of Antennas and Propagation)
The spaceborne wide-area surveillance mode, achieved by a modified TOPSAR mode, is proposed for maritime monitoring. In the proposed mode, the requirements of detecting targets from different aspect angles with a high revisit rate can be satisfied by modifying the TOPSAR mode which steers antenna in the azimuth direction. The feasibility as well as its application in maritime monitoring are validated by theoretical analysis and simulation experiments.